The circadian clock gene period regulates the composition and daily bacterial load of the gut microbiome in Drosophila melanogaster - Matteo Battistolli; Irene Varponi; Ottavia Romoli; Federica Sandrelli (Scientific Reports)
Abstract While Drosophila melanogaster serves as a crucial model for investigating both the circadian clock and gut microbiome, our understanding of their relationship in this organism is still limited. Recent analyses suggested that the Drosophila gut microbiome modulates the host circadian transcriptome to minimize rapid oscillations in response to changing environments. Here, we examined the composition and abundance of the gut microbiota in wild-type and arrhythmic per 01 flies, under 12 h:12 h light: dark (12:12 LD) and constant darkness (DD) conditions. The gut microbiota of wild-type and per 01 flies showed differences in composition, suggesting that the D. melanogaster circadian gene per has a role in shaping the gut microbiome. In 12:12 LD and DD conditions, per 01 mutants showed significant daily variations in gut bacterial quantity, unlike wild-type flies. This suggests that per is involved in maintaining the daily stability of gut microbiome load in D. melanogaster. Expanding these analyses to other fly strains with disrupted circadian clocks will clarify whether these effects originate from a circadian function of per or from its possible pleiotropic effects. Finally, some gut bacteria exhibited significant 24 h fluctuations in their relative abundance, which appeared independent from the fly circadian clock, suggesting that certain gut commensal bacteria in Drosophila may possess a host-independent circadian clock.